UJI KEMANFAATAN BIOCHAR DAN BAHAN PEMBENAH TANAH UNTUK PERBAIKAN BEBERAPA SIFAT FISIK TANAH BERPASIR SERTA DAMPAKNYA TERHADAP PERTUMBUHAN DAN PRODUKSI TEBU - Akhmad Hadi Faqih Syaikhu; Budi Hariyono; Didik Suprayogo (Jurnal Tanah dan Sumberdaya Lahan, 2016)
Sugarcane development in Indonesia has shifted to dry land to meet the needs of the national sugar. However, there are many limiting factors like sandy texture, loose structure, low water holding capacity and low nutrient availability that are required to be solved improve to support plant growth and production. Application of soil conditioner is one of the ways to improve the physical properties of a sandy soil. This study was aimed to examine the benefits of sugarcane trash biochar, boiler ash, sugarcane trash compost, and manure as an alternative soil conditioners to improve some of the physical properties of sandy soil and its relationship to the growth and production of sugarcane. Treatments tested in this study were P0= control (without soil conditioner), P1= sugarcane trash 10 t ha-1, P2 = sugarcane boiler ash 10 t ha-1, P3 = manure 10 t ha-1, P4 = sugarcane trash compost 10 t ha-1, and P5 = sugarcane trash 5 t ha-1 + manure 5 t ha-1. The results showed that all treatments increased aggregate stability with very significant compared to the control at 5-11 months after planting. The best results were shown by the treatment of 10 t ha-1 of sugarcane trash biochar that could consistently improve sandy soil aggregate stability at 5-11 months after planting. Application of biochar and others soil conditioner also significantly affectedÂ  soil bulk density, pF 4.2, available water content, penetration resistance, Lrv, plant height, stem diameter, although they did not consistently occur in the entire observation period. Overall effect of sugarcane trash biochar and others soil conditioners to physical properties of sandy soil had no effect on increasing the growth and production of sugarcane.